Tren Travelling Dalam Perspektif Maqoshid Syariah - Maulana Hamzah (Indonesian Journal of Islamic Economics and Business, 2019)
Travelling is culture beyond millenials, and It has a significant effect on tourism industry and country’s income. This paper aims to analyze the travelling culture based on islamic perspective and give the views by using maqoshid syariahs perspective. It may describe the comprehensive description by dividing maqoshids perspective into five categories, they are religion, self, intellect, family and wealth. Qualitative approach with content analysis is used in this research to analyze the connectivity between travelling culture and maqoshid. The results of this study attempt to describe traveling into the five maqoshids, namely religion, soul, mind. descent and property as traveling that brings mashlahah. Traveling which contains mudharat is religious traveling that contains of shirk, travel to unbeliver countries, travel to immoral places, tours of women without mahroms and tours of non-believers to Islamic countries with the aim of colonialism. This research also divides tourism based on the level of importance such as dhoruriyyah, haajiyah and tahsiniyyah.